1993
DOI: 10.1177/00220345930720020501
|View full text |Cite
|
Sign up to set email alerts
|

Comparative SEM and TEM Examination of the Ultrastructure of the Resin-Dentin Interdiffusion Zone

Abstract: The resin-dentin interdiffusion zone produced by a dentin-adhesive system that removes the smear layer and concurrently decalcifies superficial dentin was morphologically examined by both scanning and transmission electron microscopy. Cross-sectioned resin-bonded dentin discs were etched with an argon-ion beam to make the resin-dentin interface observable by SEM. For the TEM examination, the sections were partly decalcified by an aqueous EDTA solution to facilitate ultramicrotomy and to disclose the ultrastruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
129
1
30

Year Published

1997
1997
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 276 publications
(165 citation statements)
references
References 12 publications
5
129
1
30
Order By: Relevance
“…[2][3][4][5][6][7]20 However, there was no hybrid layer detected on the SEM image of LB. For examination of the hybrid layer using SEM and TEM, pretreatment such as etching or decalcification is often employed to make the microstructure more prominent by changing the morphology 2,6,7,21,22 . In the present study, such pretreatment was not performed because a flat surface is necessary to obtain precise EDS results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6][7]20 However, there was no hybrid layer detected on the SEM image of LB. For examination of the hybrid layer using SEM and TEM, pretreatment such as etching or decalcification is often employed to make the microstructure more prominent by changing the morphology 2,6,7,21,22 . In the present study, such pretreatment was not performed because a flat surface is necessary to obtain precise EDS results.…”
Section: Discussionmentioning
confidence: 99%
“…In current procedures to achieve bonding between resin and dentin, it is essential to form an interpenetrating network of polymer and dentinal collagen at the bonding interface; namely, a hybrid layer. 1,2 This hybrid layer is formed by a three step chemical surface treatment composed of etching, priming, and bonding. 1,2 In etching treatment, an acidic liquid removes minerals at the dentin surface and exposes the matrix collagen network.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The inter-relationship between collagen fibers and the dentinal matrix undergoes changes with demineralization 32 and aging. 33 Thus, the contribution of a frontal and/or posterior FPZ to energy dissipation during the fracture of dentin may not remain constant over the life of a tooth.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported the structure of the ABRZ [9][10][11] . The ultrastructure of the HL and ABRZ have been revealed using various treatments and analyzed using both scanning and transmission electron microscopy [12][13][14] . When considering bond degradation, the hydrolytic effects of water on adhesives is of great importance.…”
Section: Introductionmentioning
confidence: 99%